2021
DOI: 10.1111/jcmm.16345
|View full text |Cite
|
Sign up to set email alerts
|

MUC16 promotes EOC proliferation by regulating GLUT1 expression

Abstract: As a common malignancy in females with a higher incidence rate, epithelial ovarian cancer (EOC) is a heterogeneous disease with complexity and diversity in histology and therapeutic response. Although great progress has been made in diagnosis and therapeutic strategies, novel therapeutic strategies are required to improve survival. Although the promoting effect of mucin 16 (MUC16) on tumour progression has been reported, the potential mechanisms remain unclear. In our study, we reported that overexpression of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Muc16 predicts a poor prognosis in EOC [ 23 ]. Discontinuous patterns of congestive intrarenal venous flow (IRVF) (biphasic and uniphasic) predict adverse outcomes in acute heart failure (AHF), which is difficult to detect in patients with severe symptoms.…”
Section: Muc16 As a Biomarker Of Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Muc16 predicts a poor prognosis in EOC [ 23 ]. Discontinuous patterns of congestive intrarenal venous flow (IRVF) (biphasic and uniphasic) predict adverse outcomes in acute heart failure (AHF), which is difficult to detect in patients with severe symptoms.…”
Section: Muc16 As a Biomarker Of Diseasementioning
confidence: 99%
“…MUC16 enhances glucose uptake by tumor cells by promoting the expression of glucose transporter 1 (GLUT1), a glucose transporter that promotes the transport of glucose molecules across cell membranes, and promotes glycogen synthesis, thus enabling tumor cells to produce more energy for proliferation [ 23 ]. The effect of MUC16 on the inhibition of anti-apoptotic B-cell lymphoma 2 (Bcl-2) suggests that MUC16 controls AKT Serine/Threonine Kinase 1 (AKT) regulated apoptotic signaling.…”
Section: Function and Mechanism Of Muc16 In Diseasementioning
confidence: 99%
“…Since tumor metabolism has gradually emerged as a prominent research focus in anticancer therapy, it has been observed that GLUT1 exhibits abnormal expression across various tumor types. In OC, MUC16 and miR-1204 have been found to positively regulate the expression of GLUT1, thereby facilitating enhanced glucose metabolism reprogramming and glycogen synthesis for increased energy production during tumor progression 82 , 106 . This study suggests that GLUT1, serving as an energy indicator, can be utilized to assess the prognostic value for OC patients.…”
Section: Glucose Metabolism In Ocmentioning
confidence: 99%
“…Furthermore, Wang et al. found that MUC16’s regulatory effect on GLUT1 expression might be a contributing factor to the proliferation and progression of ovarian epithelial cancer ( 43 ). In terms of tumor metastasis, Huo et al.…”
Section: The Relevance Of Muc1 and Muc16 To Tumor Development And Pro...mentioning
confidence: 99%